PENGUNGKAPAN KEBERADAAN TOKOH SEMAR DALAM PROFESI AKUNTAN - Lila Alwyah; Audrie Clarissa Bepe (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This research aims to identify the characteristics of Semar's character which are reflected in the character of accountants, with a focus on the application of his professional code of ethics The method used in this research is qualitative using an interpretive paradigm. Data was obtained through interviews with auditors and accounting service office owners. This research found that the characteristics of Semar are reflected in accountants such as Manunggaling budhi, lathi and experti, devotion, role model, sense of awareness and Manunggaling kawula Gusti. This characteristic is inherent in accountants in carrying out their profession. So an accountant is not only called a